Improving the understanding of originator and biosimilar biologics among healthcare providers in Saudi Arabia - Mohammed A. Omair (Saudi Pharmaceutical Journal, 2020)
The loss of patentability of many originator biologics has led to the rapid introduction of biosimilar agents. The anticipated economic benefit of introducing such agent has been accompanied by vagueness surrounding their biotechnology, approval requirements, positioning in treatment paradigms and potential for adverse events. The Second Symposium on Biologics and Biosimilars “Beyond Clinical Practice” was held on 24th-26th January 2020 aiming at improving the understanding of these new agents in a diverse interactive conference and to guide stakeholders how to introduce biosimilars into clinical practice. The symposium consisted of 4 tracks and 3 workshops. A total of 217 participants attended the meeting. The majority were pharmacists (78.8%) followed by physicians (18.9%) and other healthcare providers (2.3%). The workshops covered the following topics: basics of pharmacoeconomics, pharmacovigilance and patients’ perspective toward biosimilar biologics. While, the 4 main tracks included: Introduction to biosimilars, challenges in clinical practice, regulatory and pharmacoeconomic aspects and Challenges in biosimilar pharmacovigilance.